In Situ Surface-Enhanced Raman Scattering Detection of a SARS-CoV-2 Biomarker Using Flexible and Transparent Polydimethylsiloxane Films with Embedded Au Nanoplates - Yue, Weiling (2023)
Coronavirus disease 2019 (COVID-19) remains an ongoing issue worldwide and continues to disrupt daily life. Transmission of infection primarily occurs through secretions when in contact with infected individuals, but more recent evidence has shown that fomites are also a source of virus transmission, especially in cold-chain logistics. Traditional nucleic acid testing for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) contamination in cold-chain logistics is time-consuming and inaccurate because of the multiplex sampling sites. Surface-enhanced Raman spectroscopy (SERS) provides a rapid, sensitive, and label-free detection route for various molecules, including viruses, through the identification of the characteristic peaks of their outer membrane proteins. In this study, we embedded arbitrarily orientated gold nanoplates (Au NPLs) in polydimethylsiloxane (PDMS) elastomer and used it as biosensor for the ultrasensitive detection of the SARS-CoV-2 spike protein in cold-chain logistics. This transparent and flexible substrate can be wrapped onto arbitrary surfaces and permits light penetration into the underlying contact surface, enabling in situ and point-of-care SERS diagnostics. The developed assay displayed high reproducibility (8.7%) and a low detection limit of 6.8 × 10-9g mL-1, indicating its potential to serve as a promising approach with increased accuracy and sensitivity for the detection of the S protein.